Leeches of the genus Helobdella (Clitellata: Hirudinida) from São Paulo, Brazil with descriptions of two new species using micro-computed tomography and a new record of Barbronia weberi (Blanchard 1897) - Iwama, Rafael Eiji; Arruda, Eliane Pintor (Zootaxa, 2016)
Leeches are an important group of macroinvertebrates found in the benthic zone of rivers, streams, lakes and ponds. Despite their ecological importance and potential as bioindicators, little is known about the diversity of leeches in Brazil, where only a few sporadic studies have been performed. Six locations in the region of Sorocaba, in the state of São Paulo, were sampled in order to study the diversity of predatory leeches. Besides traditional dissections, micro-computed tomography was used to access the internal morphology of the new species Helobdella chaviensis n. sp. and Helobdella schlenzae n. sp. Four additional native species were found and redescribed using traditional techniques. The invasive species Barbronia weberi (Blanchard 1897) was reported in the Tietê River for the first time.